Women on corporate boards: Do they advance corporate social responsibility?. (July 2018) - Cook, Alison; Glass, Christy
Do women board directors change how companies do business? Firms face growing pressure to appoint more women to their boards of directors, yet little is known about the factors that enable female directors to impact their organizations. This study analyzes the representational thresholds that facilitate women's leadership in the area of corporate social responsibility. We test the predictions of token theory and critical mass theory to evaluate the ability of women to impact firm outcomes based on their numerical representation on the board of directors. Our analysis focuses on board composition and organizational outcomes in the Fortune 500 from 2001 to 2010. Our findings challenge the theoretical assumptions that solo and token women are unable to exert significant influence over their organizations, and underscore the importance of board diversity for today's firms.